Common contact allergens implicated in frontal fibrosing alopecia found in over-the-counter hair growth serums and solutions - Kritin K. Verma, MBA; Blayne Fenner, BS; Meredith Pham, MD; Michelle Tarbox, MD, FAAD (Wolters Kluwer, 2024)
Background:. Frontal fibrosing alopecia (FFA) is a form of lichen planopilaris with an undetermined etiopathogenesis, predominantly affecting women. There is conflicting evidence as to whether contact allergens may play a role in the underlying etiology or progression of FFA. Objective:. The aim of this study is to find the most common products that patients search for online, identify contact allergens present in these advertised over-the-counter hair products, and suggest their role in the development or exacerbation of FFA. Methods:. We reviewed current research on this topic and then investigated common allergens found in over-the-counter hair products commonly used for hair regrowth. Results:. FFA's exact etiopathogenesis remains vastly unknown, however, current literature has reported an association between inflammatory skin conditions and FFA. Limitations:. The lack of published data on the function of contact allergens in FFA placed restrictions on our study. Conclusion:. A survey-based analysis with a larger cohort is needed to further interpret the relationship between product use and FFA presentation based on contact allergens. More research on possible etiopathogenesis and the relationship between contact dermatitis and FFA may prevent further progression of a patient's disease, leading to an improvement in their quality of life.